The Proofs of the Arithmetic-Geometric Mean Inequality Through Both the Product and Binomial Inequalities (European Journal of Pure and Applied Mathematics, 2018)
In this paper, we show new ways of proving the arithmetic-geometricmean AGM inequality through the first product and the second productinequalities. In addition, we prove the AGM inequality through thebinomial inequalities. These methods are alternative ways of provingAGM inequalities.